Product Innovation, Market Intelligence and Pricing Capability as a Competitive Advantage in the International Performance of Startups: Case of Peru - Gómez-Prado, Romina (2022)
“Since the COVID-19 pandemic arrived, various options have been created to export products, with the creation and development of startups becoming a viable and significant option. Previous research has described the influence of competitive business advantage on international performance. However, the novelty of the current research was to evaluate the influence of the company’s capabilities, through the competitive advantage of the company as a mediator in international performance. The study was based on the responses of 200 active startups in Peru. The PLS-SEM technique was utilized with the company’s capabilities linked to internationalization processes as independent variables, as well as market intelligence, product innovation, and pricing. The mediating variable was competitive advantage, and the dependent variable was international performance. It was found that all three capabilities influenced competitive advantage and, ultimately, international performance. It was concluded that competitive advantage does not act as a mediator between pricing capabilities and the international performance of startups. Moreover, it was determined that competitive advantage acts as a mediator between two of the three assessed capabilities: market intelligence capabilities and product innovation capabilities. The results were supported by the reflective and formative evaluation of the results obtained through the applied technique. These results could help create better programs to promote startups interested in internationalizing and exporting products.“